Estuarine Ecosystem and Climate Stressors Evaluation: Spatiotemporal NDVI Investigation on Intertidal Sedimentary Landforms - Ali K. M. Al-Nasrawi; Ameen A. Kadhim; Sarah M. Hamylton; Brian G. Jones (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
The ratio between the red (R) and near-infrared (NIR) pixel values of satellite imagery is determined by the normalized difference vegetation index or NDVI. At a landscape level, NDVI analyses the spectral wave reflections to investigate the ecosystem health through the greenish canopy dynamism as a main ecosystem’s body mass on an intertidal landform. The vegetation cover pixel values (0-255) are transformed into a -1 to +1 scale via the NDVI index. NDVIs showed vegetation canopy was clearly influenced by the coastal environments. Thus, the main environmental and climate change factors can be investigated, including temperature, precipitation, and sea level rise, that are affecting the health and distribution of coastal vegetation. Meanwhile, the runoff and sedimentation rates that can impact coastal areas are investigated as well. This study investigates vegetation canopy dynamics on three various coastal ecosystems in southeastern Australia over the past 40 years (1975-2015), as a comparison case study using NDVI index as an indicator. Landsat 1-8 satellite imagery is used to drive temporal-datasets into NDVI values. These values were then regressed to the climatic and geomorphic variables. At the study sites, results show a clear increase in NDVI at Towamba and Wandandian estuaries, compared to a slight decline at Comerong Island (southeastern Australia). The most significant positive impact on NDVI was the sedimentation rate since it has the potential to provide additional space for vegetation. Except on Comerong Island, the temperature and sea level rise have positive effects as well, but rainfall has no significant effect on the NDVI at any site. Different NDVI trends have been recorded at these three coastal sites reflecting different correlations between the vegetation, climatic and geomorphic (as independent) variables. The largest impact on vegetation cover and, hence, on NDVI was the geomorphological characteristics of such highly dynamic intertidal estuarine landforms, which are subject to active erosion and deposition processes. Using NDVI as an evaluation tool to assess the vegetation cover has produced temporal-dynamic datasets that are correlated with the primary environmental factors. Using this approach, resource managers will be able to assess the possible effects of any environmental changes and then make more informed decisions for conservation sustainability plans.